Entry into the lytic cycle exposes EBV-infected cells to NK cell killing via upregulation of the MICB ligand for NKG2D and activation of the CD56bright and NKG2A+KIR+CD56dim subsets - Desimio, Maria Giovanna; Covino, Daniela Angela; Cancrini, Caterina; Doria, Margherita (Frontiers in Immunology, 2024)
The Epstein–Barr virus (EBV) is usually acquired during infancy as an asymptomatic infection and persists throughout life in a latent state under the control of the host immune system. However, EBV is associated with various malignant diseases that preferentially develop in immunodeficient individuals. Accumulating evidence suggests an important role for NK cells, though the mechanisms by which EBV evades or triggers NK cell responses are poorly understood. Here, we generated EBV-immortalized lymphoblastoid cell lines stably expressing an inducible form of the BZLF1 early lytic viral protein (LCL-Z) to challenge primary NK cells with EBV+ targets in either the latent or lytic phase of infection. We show that entry into the lytic phase results in drastic downregulation of HLA-E but not HLA-A, -B, and -C molecules and in increased expression of ligands for the activating NKG2D receptor, with MICB being upregulated at the cell membrane and released in a soluble form while ULBP2 and ULBP4 accumulate intracellularly. Furthermore, LCL-Z cells are killed by NK cells in an NKG2D-dependent manner and to a much higher extent during the lytic phase, but HLA-class I molecules constrain killing throughout the viral life cycle; unexpectedly, the antibody-mediated block of the inhibitory NKG2A receptor results in reduced lysis of lytic LCL-Z cells that are nearly devoid of the cognate HLA-E ligand. Accordingly, we show that NKG2A+ NK cell subsets, specifically CD56bright and NKG2A+KIR+CD56dim cells, are those that preferentially respond against cells with lytic EBV replication. Overall, these results shed light on NK/EBV+ cell interactions providing new information for improving NK cell-based immunotherapies to treat EBV-induced diseases.